Identification of carbohydrate active enzymes from whole genome sequence of Tilletia indica and sporulation analysis - SINGH, JAGMOHAN; AGGARWAL, RASHMI; GURJAR, MALKHAN SINGH; SHARMA, SAPNA; SAHARAN, M S (The Indian Journal of Agricultural Sciences, 2019)
Karnal bunt of wheat is an internationally quarantined disease. One of the major constraints in exporting wheat is prevalence of Karnal bunt (KB). It is caused by Tilletia indica which is a heterothallic fungus and requires fusion of different mating types for causing infection. The growth efficiency and aggressiveness of plant pathogens are often associated with their carbohydrate active enzymes (CAZymes). The present study was undertaken to identify the CAZymes in whole genome sequence of Tilletia indica, and conduct sporulation analysis. Total 315 predicted secretory proteins were annotated with the CAZyme database (dbCAN). The secreted carbohydrates active enzymes were identified as 105 glycosylhydrolases (GH), 85 glycosyltransferases (GT), 83 carbohydrate esterases (CE), 8 carbohydrate binding modules (CBM), 30 auxiliary activities (AA) and 4 polysaccharide lyases (PL). Based on sporulation analysis of T. indica isolates, KB1 and KB2 isolates were most sporulative among all the isolates of T. indica. These carbohydrate active enzymes can help to understand the pathogenesis mechanism(s) of Karnal bunt using functional genomics approach.